Effects of prior antiplatelet use on futile reperfusion in patients with acute ischemic stroke receiving endovascular treatment. (March 2023) - Sohn, Jong-Hee; Kim, Chulho; Lee, Minwoo; Kim, Yerim; Jung Mo, Hee; Yu, Kyung-Ho; Lee, Sang-Hwa
Introduction: We evaluated the effects of prior antiplatelet use (APU) on futile reperfusion (FR) after endovascular treatment (EVT) in acute ischemic stroke. Material and methods: We consecutively collected data of 9369 patients with acute ischemic stroke from four university-affiliated multicenter registry databases over 92 months. We enrolled 528 patients with acute stroke receiving EVT. Among them, we defined FR in subjects as a 3-month modified Rankin Scale score of >2 despite successful reperfusion after EVT. We classified patients into two groups: prior APU and no prior APU. We used propensity score matching (PSM) to overcome the imbalance in multiple covariates between the two groups. After PSM, we compared the baseline characteristics between the two groups and performed multivariate analysis to determine whether prior APU affected FR and other stroke outcomes. Results: The overall FR rate in the present study was 54.2%. In the PSM cohort, the FR was lower in the prior APU group than that in the no prior APU group (66.2% vs 41.5%, p < 0.001). In the multivariate analysis using the PSM cohort, prior APU significantly reduced the risk of FR (odds ratio (OR), 0.32; 95% confidence interval (CI), 0.18–0.55; p = 0.001) and stroke progression (OR, 0.38; 95% CI, 0.15–0.93; p = 0.03). Prior APU was not associated with symptomatic hemorrhagic transformation in this study. Conclusion: Prior APU potentially reduced FR and stroke progression. Further, prior APU was not associated with symptomatic hemorrhagic transformation in patients receiving EVT. APU pretreatment can be a modifiable predictor of FR in clinical practice.